(untitled) (Research, Society and Development, 2020)
The concern of consumers for healthier food products grows more and more. Therefore, it is extremely challenging for the food industry to find ways to satisfy this new market niche through new processes and products that use less or anyone chemical additives and at the same time have better nutritional characteristics. Breads are among the most consumed bakery products worldwide. Originally, they were produced by natural fermentation, a process capable of providing more flavor and increasing its shelf life. The aim of this work was to evaluate the production of sourdough breads with a Brazilian natural fruit pulp, called araticum. Natural starter was evaluated for lactic acid bacteria count and pH. The breads were evaluated regarding specific volume, instrumental color, water activity, moisture content, instrumental texture, antioxidant capacity, pH and total titratable acidity, slices images and sensory properties. The results were statistically evaluated by analysis of variance (ANOVA) and comparison of means (HSD Tukey test) with 95 % of confidence. The sourdough breads with araticum fruit pulp showed a lower specific volume and higher crumb firmness, antioxidant activity and acceptance by the consumers, when compared to the standard formulation. These results suggest that natural fermentation is a promising technology to be used, resulting in a commercially viable product.